Protein-coated polymer as a matrix for enzyme immobilization: immobilization of trypsin on bovine serum albumin-coated allyl glycidyl ether-ethylene glycol dimethacrylate copolymer - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Kumaraguru, Thenkrishnan; Bajja, Sreedhar; Fadnavis, Nitin W.; Addepally, Uma; Rajdeo, Kishor; Ponrathnam, Surendra; Deokar, Sarika Babasaheb (Biotechnology Progress, 2014)
Allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) shows excellent bovine serum albumin (BSA) adsorption (up to 16% (w/w)) at pH 8.0 and the adsorbed BSA is strongly bound. This protein-coated polymer provides a novel matrix with naturally existing functional groups such as thiol, amino, and carboxylic acid that are available for covalent immobilization of functional enzymes. Employing appropriate strategies, trypsin as a model protein was covalently bound to BSA-coated matrix both independently, and in a stepwise manner on the same matrix, with less than 5% loss of enzyme activity during immobilization. Glutaraldehyde crosslinking after immobilization provide stable enzyme preparation with activity of 510 units/g recycled up to six times without loss of enzyme activity. AFM studies reveal that the polymer surface has protein peaks and valleys rather than a uniform monolayer distribution of the protein and the immobilized enzyme preparation can best be described as polymer supported cross-linked enzyme aggregates (CLEAs). (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:317-323, 2014
Keywords: allyl glycidyl ether; Bovine serum albumin; ethylene glycol dimethacrylate; Immobilization; Trypsin

Regioselective acylation of 2-methoxy naphthalene catalyzed by supported 12-phosphotungstic acid - Kumaraguru, Thenkrishnan; Devi, Ayala Vedamayee; Siddaiah, Vidavalur; Rajdeo, Kishor; Fadnavis, Nitin W. (Applied Catalysis A-General, 2014)
12-Phosphotungstic acid supported on silica gel, zirconium sulfate, and a combination of silica gel and zirconium sulfate (50% w/w) were employed as solid acid catalysts for regioselective acylation of 2-methoxynaphtalene with acetic anhydride. 1-(6-Methoxynaphthalen-2-yl)ethanone (2,6-AMN), a commercially important intermediate for production of Naproxen, was obtained with excellent selectivity (>98%) at 67-68% conversion using 12-phosphotungstic acid supported on silica gel 20% (w/w) in refluxing tetrachloroethane. The unreacted starting material can be easily separated from the product by a simple crystallization from nonane. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Acylation; Naproxen; Phosphotungstic acid; Silica gel; Supported; Zirconium sulfate